Late-onset traumatic corneal flap dislocation and secondary epithelial ingrowth 24 years after LASIK - Xu Zhang; Huixian Wang; Xiaowei Gao; Wenjing Li (American Journal of Ophthalmology Case Reports)
Purpose: To analyze the diagnostic process, treatment, and post-operative outcomes of a unique case involving a late-onset (24 years post) traumatic corneal flap displacement after Laser-assisted in situ keratomileusis (LASIK) surgery due to a plant-related trauma. with an emphasis on the accompanying extensive epithelial ingrowth beneath the flap. Observations: A 59-year-old male patient experienced corneal flap displacement 24 years post-LASIK due to a minor plant-related trauma. This case was complicated by extensive epithelial ingrowth beneath the flap, which was initially misdiagnosed with fungal keratitis. Upon identification of the actual cause, corneal flap repair surgery was performed, leading to partial vision recovery. Conclusions and importance: This case signifies the potential for LASIK flap displacement even decades post-surgery due to minor traumas and highlights the need for vigilance in diagnosing associated complications like epithelial ingrowth. It indicates the importance of ophthalmologists and clinicians being vigilant for such complications and necessitates their familiarity with basic management techniques or quick referral to a corneal refractive surgery specialist. This report of a 24-year interval between LASIK and traumatic flap displacement with epithelial ingrowth is one of the longest known. The case also demonstrates that patients with late flap displacement can regain significant visual acuity with timely and appropriate management.